Tingkat Pengetahuan Sikap Dan Tindakan Petani Tentang Penggunaan Alat Pelindung Diri Di Subak Cepik Kabupaten Tabanan Tahun 2019 - Indriana, Kadek Nanda Bella; Asmara, I Wayan Suarta; Aryasih, I Gusti Ayu Made; Posmaningsih, D.A.A (Poltekkes Kemenkes Denpasar, 2020)
Abstract : Farmers are the largest working group in Indonesia. The level of farmers' exposure to the use of pesticides is highly dependent on how knowledge is used in using pesticides. Tabanan Regency is one of the districts in Bali. The area of paddy in Tabanan Regency reaches 22,453 hectares which is the widest rice field area and at the same time as a rice barn in Bali Province. The purpose of this study was to determine the knowledge, attitudes, and actions of farmers in the use of personal protective equipment. The method used is descriptive, primary data obtained through interviews and direct observation using questionnaires and secondary data obtained from the village head in the form of population data. The results of the study revealed that 18 respondents (29%) had sufficient knowledge and 45 respondents (71%) had good knowledge. As many as 2 respondents (3%) who had less attitudes, 36 respondents (57%) who had enough attitudes, and 25 respondents (40%) who had good attitudes. And as many as 57 respondents (90%) who have less action, 6 respondents (10%) who have enough action. Conclusion in this study farmers have good knowledge, but attitudes and actions to use personal protective equipment when direct contact with pesticides is still lacking.